Peygamberlik ve soy ilişkisi - Başkır, Meryem (Fırat Üniveristesi, 2026)
Bu çalışmada amaç; öncelikle Kur'an ekseninde peygamberliğin soy/zürriyet bağlantısını incelemektir. Çünkü Peygamberlikle ilgili en gerçek bilgiye Kur'an'dan ulaşabiliriz. Konuyu peygamberlik ve zürriyet kavramları çerçevesinde Kur'an'dan gerekli incelemeyi yaparak tarihsel bağlamla ilişkisini kurmaya çaba sarf ettim. Temel kaynak olarak Kur'an ayetleri, çalışmamıza yarar sağlayan diğer kaynak ve eserler neticesinde literatüre katkı sağlayacak bir tez ortaya koymaya çalıştım. Araştırmamızda ilk olarak tarihte ve dini geleneklerde peygamberliğin biyolojisi ve şeceresi başlığı altında Sümerlerde, Yahudilikte, Hıristiyanlıkta ve İslam'da peygamberlik olgusu incelenmiştir. Kutsal kitaplar öncesinden başlayarak kutsal kitaplarda peygamberlerin soyu, ilk doğan erkek çocuklarının ayrıcalıklarının neler olduğu ele alınmıştır. İlk doğan çocuğun mabede adanması geleneğinin ve ilk doğum erkek çocuğunu belirlemede babanın tercihinin ve bu tercihin siyaset alanı dışında peygamberliğin oluşumunda da babadan oğula geçmesinde rolü olup olmadığı araştırılmıştır. İbrahim'in (a.s.) soyundan gelecek olanlara duası soyun devamının önemine işaret olabilmekle birlikte Peygamberlik geleneğinde ilk doğum ve güçlü ailelerin dini yayma konusundaki etkisi de olabileceği incelenmiştir. Kur'an'da ilk doğan çocuk peygamber olur diye bir ibare yok fakat tarihte bu hususa dair anlatımlar var bunun sosyolojik olarak peygamberlikle de ilişkisi olup olamayacağı araştırılmıştır. Peygamber'in (a.s.) tek çocuk olması, soyunun İsmail'e (a.s.) dayandırılması arasındaki ilişki değerlendirilerek Peygamberliğin doğrudan doğruya hiçbir kural olmadan Allah'ın seçimi mi olduğu yoksa toplumların geleneklerinde var olan birtakım kuralların ve soyun bu seçimde etkisinin imkânı üzerinde çalışılmıştır. Meryem'in (a.s.) mabede adanması, kadınlardan peygamber olması Kur'an'daki örnekleri bağlamında itikadi mezhepler açısından değerlendirilmiştir. Peygamberliğin sonuyla ilgili telakkiler başlığında İsa'nın (a.s.) göğe yükselişi, mehdi/mesih anlayışı nübüvvet ve soy ilişkisi çerçevesinde değerlendirilmiştir. Muhammed'in (a.s.) zürriyetinin nübüvvetle ilişkisi araştırılıp peygamberliğin sonuyla olan bağlantısı incelenmiştir. Bilhassa çalışmamızda tarihten bu yana tarihsel, dini ve sosyolojik olarak dini otoritenin seçilmesinde ilk doğum ve soy ilişkisi çözümlenmiştir.

The primary aim of this study is to examine the connection between prophethood and lineage/offspring within the framework of the Quran. This is because the most accurate information regarding prophethood can be found in the Quran. I have attempted to establish a historical context by examining the concepts of prophethood and lineage within the Quran. Using Quranic verses as the main source, along with other sources and works that have been helpful in this study, I have strived to present a thesis that will contribute to the literature. Our research first examines the biology and genealogy of prophethood in history and religious traditions, focusing on the phenomenon of prophethood in Sumer, Judaism, Christianity, and Islam. Starting from the pre-holy scriptures, the lineage of prophets in the holy scriptures and the privileges granted to firstborn male children are discussed. The tradition of dedicating the firstborn child to the temple, the father's preference in determining the firstborn male child, and whether this preference played a role in the transmission of prophethood from father to son, outside the political sphere, are investigated. While the prayer of Abraham (peace be upon him) for his descendants may point to the importance of the continuation of the lineage, it has also been examined in the context of prophetic tradition, considering the influence of firstborns and strong families on the spread of religion. Although the Quran does not explicitly state that the firstborn child will be a prophet, historical accounts of this exist, and its sociological connection to prophethood has been investigated. The relationship between the Prophet's (peace be upon him) being an only child and his lineage being traced back to Ishmael (peace be upon him) has been evaluated to determine whether prophethood is a direct choice by God without any rules, or whether certain rules and lineage within societal traditions may have influenced this selection. The dedication of Mary (peace be upon her) to the temple and the emergence of female prophets have been evaluated from the perspective of different schools of thought within the context of Quranic examples. Under the heading of conceptions concerning the end of prophethood, the ascension of Jesus (peace be upon him) to heaven and the understanding of the Mahdi/Messiah have been evaluated within the framework of the relationship between prophethood and lineage. This thesis investigates the relationship between the lineage of Muhammad (peace be upon him) and prophethood, examining its connection to the end of prophethood. Specifically, it analyzes the historical, religious, and sociological aspects of the relationship between birth and lineage in the selection of religious authority throughout history.
Relationship between prophethood and lineage
Keywords: Din